FEATURES OF PUBLIC PROCUREMENT IN EXTREME CONDITIONS OF STATE FUNCTIONING (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article reveals the role of public procurement in the public finance system of Ukraine in the extreme conditions of its operation in the last 15 years and the need to overcome the long-term consequences of the coronavirus pandemic and Russia's war against our country. The need to strengthen state regulation of this process is emphasized, since in the extreme conditions of the functioning of Ukraine, only the state can effectively resist the specified challenges, as well as the so-called "black swans". At the same time, the erroneous transfer of the so-called military tax on citizens' incomes from the budgets of local self-government bodies to the State Budget of Ukraine in 2024 is emphasized, which contradicts the provisions of the Budget Code of Ukraine.The authors also analyzed the features of public procurement in the EU countries to eliminate the consequences of the coronavirus and the energy blockade of the countries of the European Union by Russia after its war against Ukraine. It is emphasized that in these conditions EU countries accelerate the implementation of "green" projects and allocate additional funds for them, which is important to take into account in Ukraine in the process of rebuilding its economy.The article examines the problems that exist in Ukraine under martial law when conducting tender procurements and taxing their Ukrainian participants, as well as problems in the activities of the country's controlling structures in the field of public procurement control and planned ways to overcome them, taking into account the experience of the countries of the European Union. primarily Poland. It is emphasized that a significant part of the problems in the defense sphere of Ukraine can be solved by innovative entrepreneurship with a significant increase in public orders for similar products.The authors also substantiate the directions of reforming the mechanism of public procurement in Ukraine in the conditions of reconstruction, taking into account the experience of the EU countries regarding measures to introduce the European Green Course; identified financial positives and problems of public procurement after the entry into force of the new version of the Law of Ukraine "On Public Procurement"; researched forms of financial responsibility of participants and customers of public procurement in Ukraine under martial law and their effectiveness.
Keywords: extreme conditions, coronavirus pandemic, Russia's war against Ukraine, public procurement